STATISTICAL ANALYSIS OF RYE YIELD IN UKRAINE - Гізетдінов, Едуард; Чухліб, Алла (SWorldJournal, 2023)
The article provides а retrospective analysis of rye yield in Ukraine. Methodical aspects of revealing the tendency of change of productivity of rye by the way of analytical alignment are considered. The statistical analysis of rye yield in Ukraine is co